2005
DOI: 10.3354/meps294063
|View full text |Cite
|
Sign up to set email alerts
|

Non-synergistic effects of water-soluble crude oil and enhanced ultraviolet-B radiation on a natural plankton assemblage

Abstract: The present study demonstrates the effects of the water-soluble fraction (WSF) of a crude oil, enhanced ultraviolet-B radiation (UVBR: 280 to 320 nm), and the combination of WSF and enhanced UVBR on a natural plankton assemblage (<150 μm) isolated from the lower St. Lawrence Estuary. To study the separate and dual effects of WSF and UVBR, 12 microcosms (9 l) were immersed in the water column of larger mesocosms (polyethylene bags; 1800 l), providing 4 treatments, each in triplicate: (1) NUVBR + WSF (natural UV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 66 publications
3
24
1
Order By: Relevance
“…Pigment analyses confirmed such a change in exposed communities; diatoms were left to dominate the 250 nmol l -1 community together with green algae, whereas prymnesiophytes and cryptophytes declined compared to the control community. This is in contrast to other findings, in which diatoms were found to be more sensitive to a mixture of hydrocarbon compounds than other algal groups (Nayar et al 2005, Sargian et al 2005. The discrepancy may be caused by the more complex contamination used in those studies, or to the 'rough' characterisation of phytoplankton communities by the pigment analyses used in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Pigment analyses confirmed such a change in exposed communities; diatoms were left to dominate the 250 nmol l -1 community together with green algae, whereas prymnesiophytes and cryptophytes declined compared to the control community. This is in contrast to other findings, in which diatoms were found to be more sensitive to a mixture of hydrocarbon compounds than other algal groups (Nayar et al 2005, Sargian et al 2005. The discrepancy may be caused by the more complex contamination used in those studies, or to the 'rough' characterisation of phytoplankton communities by the pigment analyses used in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Diatoms dominated the communities after pyrene exposure at the expense of cryptophytes and dinoflagellates, which were more sensitive to pyrene. These results are consistent with our previous study (Hjorth et al 2007), but contrary to other findings (Nayar et al 2005, Sargian et al 2005. The combination of low total photosynthetic activity and high algal specific activity up until Days 4 through 5 for Py and NuPy communities usually suggests a shift in species composition towards more tolerant species (Hjorth et al 2007).…”
Section: Discussionsupporting
confidence: 91%
“…At first, abundance values were within the range observed before the spill. This result agrees with other field studies in open waters (Delille & Siron 1993) but contrasts with those reported for laboratory experiments with oil-treated microcosms, in which total number of bacteria increased significantly after contamination with water soluble hydrocarbons (Medina-Bellver et al 2005, Sargian et al 2005. Such difference could be due not only to the variable toxicity of the different hydrocarbons involved in each case study, but also to their concentrations and time of exposure for the bacterioplankton.…”
Section: Bacterioplankton Responsesupporting
confidence: 88%